Rancang Bangun Perangkat Lunak Lelang Vendor Barang dan Jasa Berbasis Website - Yesni Malau; Eni Pudjiarti; Ahmad Setiadi; Wahyutama Fitri Hidayat (LPPM Universitas Bina Sarana Informatika, 2025)
Conventional vendor selection in a project often faces various problems, such as granting exclusive rights to certain vendors, wasting time and costs, and a lack of transparency that can lead to potential corruption. This study aims to develop a website-based vendor selection system using the Codeigniter framework to improve order and transparency in the vendor selection process. The methods used include collecting user requirements data, designing the system using the PHP programming language and the Codeigniter framework, and comprehensive system testing through a Black Box Testing approach. The test results show that all features of the website-based procurement system function as expected with 100% valid results. This software aims to reduce unethical practices and increase user satisfaction and productivity by providing a faster and more transparent procurement process. This study provides a real solution to improve the vendor selection tender process and is expected to be widely implemented to support order and transparency in procurement across various sectors. In addition, this system is also expected to improve data accuracy and accelerate the decision-making process in procurement.